PENANGGULANGAN TINDAK PIDANA SIBER BERDASARKAN UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Rudy Gunawan Bastari (LP3M, 2023)
This research aims to explore and understand the law enforcement processes in addressing cybercrime in Indonesia. The research methodology combines juridical and empirical approaches by analyzing the content of the Electronic Information and Transactions Law (UU ITE) and involving the analysis of current data related to cybercrime, public responses, and the effectiveness of law enforcement. The research results provide an overview of the challenges faced in the efforts to enforce the law against cybercrime, including the lack of legal and moral awareness in society. Additionally, this research also aims to design and propose efforts to combat cybercrime in Indonesia in the future. This identification opens the door for regulatory updates and comprehensive legal awareness improvements to strengthen the efforts against cybercrime in the future.